2021
DOI: 10.1142/s0129183122500310
|View full text |Cite
|
Sign up to set email alerts
|

Information spreading on metapopulation networks with heterogeneous contacting

Abstract: Extensive real-data reveals that individuals exhibit heterogeneous contacting frequency in social systems. We propose a mathematical model to investigate the effects of heterogeneous contacting for information spreading in metapopulation networks. In the proposed model, we assume the number of contacting (NOC) distribution follows a specific distribution, including the normal, exponential, and power-law distributions. We utilize the Markov chain method to study the information spreading dynamics and find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Markovich et al(2020) considered tight centrality as a measure of node leadership, and then investigated the impact of node and community leadership on information dissemination. Nie et al(2022) considered the individual contact ability distribution, and found that the larger the mean of the individual contact ability distribution, the higher the information prevalence. Gong et al(2023) proposed the UHIR (Unknown, Hibernated, Infected, Removed) model, which combines the hyper-network model with the SEIR model to establish an online social hyper-network information dissemination model based on user and information attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Markovich et al(2020) considered tight centrality as a measure of node leadership, and then investigated the impact of node and community leadership on information dissemination. Nie et al(2022) considered the individual contact ability distribution, and found that the larger the mean of the individual contact ability distribution, the higher the information prevalence. Gong et al(2023) proposed the UHIR (Unknown, Hibernated, Infected, Removed) model, which combines the hyper-network model with the SEIR model to establish an online social hyper-network information dissemination model based on user and information attributes.…”
Section: Introductionmentioning
confidence: 99%